Physiological quality of seeds of lowland rice submitted to organic acids (Revista de Ciências Agroveterinárias, 2010)
The aim of this study was to determine the effects of six concentrations (zero; 0.017; 0.034; 0.068; 0.136 and 0.272 mol L-1) of acetic and propionic acids in the physiological quality of rice cv. BR IRGA 409 seeds. The following itens were evaluated: germination, first count of germination, emergency speed index, seedling emergence, electrical conductivity, length and dry biomass of shoot and root, total chlorophyll and leaf area. The increase in concentration of both acids decreased germination, first germination counting, emergence speed index of seedlings, and seedlings emergence. The electrical conductivity was significantly increased by increased concentrations of acids. The lengths of shoot and roots was affected in the highest concentrations (0.068 mol L-1). The dry biomass of shoot and root decreased from the concentration of 0.068 mol L-1. In general, the acetic acid has harmed the physiological quality of the rice seeds more than propionic acid.
Keywords: Oryza sativa L.; BR IRGA 409; Acetic acid; Propionic acid; Vigor; Viability; Abiotic stress.